Analisis Peran Motivasi dan Usia dalam Menentukan Pengaruh Faktor Kepemimpinan Ketua Stmik Terhadap Kinerja Pegawai - Ari Lestari (Syntax Idea, 1907)
Leadership is a form of relationship between the leader themselves, employees, and the existing situation. Leadership involves the uneven distribution of power between the leader and their members and can guide their members. Leadership can be seen as a way for a leader to coordinate all elements and parts within their community to achieve a desired organizational goal, thereby maximizing employee performance. In general, this research aims to empirically prove the influence of leadership at STMIK (College of Computer Science and Information Management) on the performance of employees by examining the tested moderating variables. The hypothesis in this study is the alternative hypothesis, which states that there is an influence of the Chairman's leadership on the effectiveness of employee performance. The results of this study indicate that the validity and reliability tests were valid and reliable. Leadership of the chairman, based on linear regression analysis, was found to be significant. The chairman's leadership has a positive and significant influence on job performance, and the determination coefficient value indicates the effectiveness of linear regression, showing a significant relationship between the chairman's leadership and job performance. Meanwhile, the variables of motivation and age were found to moderate the relationship between the chairman's leadership and employee job performance.